Flexible, student-centred remote learning for programming skills development. Issue 3 (16th March 2022) - Rowlett, Peter; Corner, Alexander S.
Abstract : During the COVID-19 pandemic, the teaching of programming for undergraduate mathematicians was moved online. This was delivered asynchronously, with students working through notes and exercises and asking for help from staff via online messages as needed. Staff delivery time was redirected from content delivery into a formal system of formative assessment, which replaced informal discussion and feedback during in-person classes. Formative tasks were submitted and feedback was provided via GitHub Classroom. Students were broadly positive about the formative feedback system and mixed about the need for live delivery. Formal formative feedback highlighted that students may hold incorrect views about the accuracy of task completion, making formal formative submission an effective use of staff delivery time.